ANALISIS PEMBELAJARAN BERBASIS EKOPEDAGOGIK UNTUK MENUMBUHKAN KARAKTER EKOLOGIS SISWA DI SEKOLAH LINIMASA - Fadhialah Hijriyanah, Dinda; Sutarna , Nana (ATTA`DIB, 2025)
Ecopedagogy is an education that teaches how learners have a reciprocal relationship with their surrounding nature by fostering ecological character values, namely a love for the environment to protect and care for nature and all its contents with a sense of responsibility. This research is motivated by the process of eco-pedagogical education and the impact of its implementation in fostering the ecological character of students at Sekolah Linimasa. This research uses a descriptive approach with a qualitative method. The participants in this study consisted of 3 teachers and 39 students from grades IV, V, and VI, using interview techniques and the distribution of questionnaires. Data was analyzed qualitatively using the Miles and Huberman model, following steps that include data collection, data display, and conclusion drawing/verification. The results of this research obtained data on the implementation of eco-pedagogical learning at Sekolah Linimasa through habituation practices such as outings, which include tracking or hiking, planting plants around the school, and bringing lunch and water bottles from home. Meanwhile, the results of the questionnaire indicate that the ecological character of students from the eco-pedagogical learning outcomes at SekolahLinimasa falls into the good category, achieving a score of 70.72%.